Estimating households and populations from primary care electronic health records: comparison with Office for National Statistics Census 2021 aggregated estimates - Wilk, Marta; Harper, Gill; Firman, Nicola; Dibben, Chris; Fry, Rich; Dezateux, Carol (International journal of population data science, 2025)
IntroductionUp-to-date, high-quality estimates of population and households are essential for planning the provision of local and central infrastructure. ObjectivesWe aimed to derive estimates of population size, and household numbers and size on Census date (21/03/2021) using north-east London primary care Electronic Health Records (EHR) and calculate levels of their agreement with the publicly available official Census 2021 estimates to assess if health data have the potential to be used to create reliable statistics. MethodsWe compared EHR and Census population estimates by sex, age, local authority, and IMD quintile, and EHR and Census household estimates by number, size, and local authority. We estimated 95% Limits of Agreement between EHR and Census household and population estimates using the Bland and Altman method. In sensitivity analyses, we excluded people with no General Practice encounter within 12 months and compared the adjusted population's size to Census estimate. We compared EHR and administrative Statistical Population Dataset (SPD) to Census population estimates by sex and age, and EHR and Admin-based Occupied Address Dataset (ABOAD) to Census household estimates by local authority and household size. ResultsEHR population estimate was 2,130,965, i.e. 7.1% higher than Census of 1,990,087. EHR household estimate was 658,264, i.e. 9.1% lower than Census of 724,045. The estimate of population with recent GP encounter was 11.6% lower than the Census estimate. Compared to Census, both SPD and EHR overcounted population of males (10.7%, 7.9% respectively) and females (3.6%, 2.7% respectively). Both ABOAD and EHR had undercounted households compared to Census (-7.3%; -9.1% respectively). ConclusionsReliable, up-to-date populations and households estimates can be derived from health records. High residential mobility increases the complexity of deriving these estimates. Excluding people without GP encounters does not improve agreement with Census. Future work will focus on comparing Census and EHR estimates using individual-level data.